The Downregulation of eIF3a Contributes to Vemurafenib Resistance in Melanoma by Activating ERK via PPP2R1B - Jiang, Shi-Long; Wang, Zhi-Bin; Zhu, Tao; Jiang, Ting; Fei, Jiang-Feng; Liu, Chong; Luo, Chao; Cheng, Yan; Liu, Zhao-Qian (Frontiers in Pharmacology, 2021)
Vemurafenib, a BRAF V600E inhibitor, provides therapeutic benefits for patients with melanoma, but the frequent emergence of drug resistance remains a challenge. An understanding of the mechanisms underlying vemurafenib resistance may generate novel therapeutic strategies for patients with melanoma. Here, we showed that eIF3a, a translational regulatory protein, was an important mediator involved in vemurafenib resistance. eIF3a was expressed at significantly lower levels in vemurafenib-resistant A375 melanoma cells (A375R) than in parental A375 cells. Overexpression of eIF3a enhanced the sensitivity to BRAF inhibitors by reducing p-ERK levels. Furthermore, eIF3a controlled ERK activity by regulating the expression of the phosphatase PPP2R1B via a translation mechanism, thus determining the sensitivity of melanoma cells to vemurafenib. In addition, a positive correlation between eIF3a and PPP2R1B expression was also observed in tumor samples from the Human Protein Atlas and TCGA databases. In conclusion, our studies reveal a previously unknown molecular mechanism of BRAF inhibitor resistance, which may provide a new strategy for predicting vemurafenib responses in clinical treatment.